1930
DOI: 10.1021/ja01374a061
|View full text |Cite
|
Sign up to set email alerts
|

The Chlorine Derivatives of Vanillin and Some of Their Reactions

Abstract: The same products were obtained in another experiment in which 0.5 cc. of piperidine was used as a catalyst.Azobenzene and p-Thiocresol.-A solution of 18.2 g. (0.1 mole) of azobenzene and 37.2 g. (0.3 mole) of £-thiocresol in 200 cc. of xylene was refluxed for twenty-five hours. As in all other experiments, a trap2 was used to exclude air. The products obtained were 9.5 g. of aniline, 0.1 g. of benzidine (from a sulfuric acid treatment of the hydrazobenzene present), 5.5 g. of £-thiocresol and 90% of the di-p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

1970
1970
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…0.5%) of 4,5,6trichloroguaiacol formed by chlorination of guaiacol existing as a minor impurity in the vanillin. A product completely free of 4,5,6-trichloroguaiacol was obtained by converting the CV to its tri-O-acetate (37), crystallizing this to purity from methanol and hydrolyzing the product with methanolic KOH. The free phenol was liberated by acidification and recrystallized from acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…0.5%) of 4,5,6trichloroguaiacol formed by chlorination of guaiacol existing as a minor impurity in the vanillin. A product completely free of 4,5,6-trichloroguaiacol was obtained by converting the CV to its tri-O-acetate (37), crystallizing this to purity from methanol and hydrolyzing the product with methanolic KOH. The free phenol was liberated by acidification and recrystallized from acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of a trichloroguaiacol from 2,6-dichlorovanillin (IIc) is unlikely, äs previous studies have shown that chlorination of IIc with sulfuryl Chloride yielded trichloro- vanillin and unreacted starting material (Raiford and Lichty 1930;Hyötyläinen and Knuutinen 1993). Reaction of 5,6-dichlorovanillin (Hd) with l equiv.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the aromatic proton signal and the carbon Signals were distinct from those of the 3 known trichloroguaiacols, although both isomers Ic and Id had similar melting points (103-4 °C and 102-4°C respectively). Raiford and Lichty (1930) found that Chlorination of 2-chlorovanillin with chlorine in Chloroform gave, besides 2,5-dichlorovanillin, a red oil which probably contains the crude trichloroguaiacol Ic. The trichloroguaiacol Ic would best be obtained by reaction of 2,5-dichlorovanillin with 0.5 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Chloro-4,5-di(phenylmethoxy)benzaldehyde (1a) [16,36,37], 3-chloro-4,5-di(phenylmethoxy)benzaldehyde (1b) [16,37,38], and 3-chloro-4,5-dihydroxybenzaldehyde (1c) [16,37,38] were prepared according to the literature. A solution of 29.8 g (content of 2a: 84%, 66.5 mmol) of crude 2a, 16.3g (43.51 mmol) of (MBE) 2 O, and 450 mg of triphenylphosphine hydrobromide in 450 ml of CH 2 Cl 2 was stirred for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%